Organizational implications on the use of outsourcing for marketing focus - Lancaster Díaz, Eduardo; Martínez Prats, Germán; Mapen Franco, Fabiola de Jesús; García Jiménez, Alejandra de Jesús (Tópicos de marketing, 2021)
Outsourcing is addressed in this document, as a strategy to increase productive and competitive efficiency in organizations. So, through this strategy companies may focus also on their marketing strategies to increase their market participation. Though, initially it was established as a way on whichorganizations had the chance to focus on their core activities and outsource those non-core ones with the intention of facing changing economic scenarios more effectively. But in the practice, this strategy involves organizational challenges, which has generated discussion about its implementation. The objective of this document is to present the challenges and organizational implications that the use of outsourcing represents in companies that have implemented this kind of strategy. It is concluded that the implementation of outsourcing reveals the need to accompany this strategy with organizational measures that help to: (1) materialize the advantages of its use, and (2) reduce the disadvantages of its use, especially those that refers to the precariousness of employment.